Upaya Pencegahan Early Dating pada Siswa di SDN 2 Banjararum Singosari Kabupaten Malang - Devy Probowati; Rizka Apriani; Arbin Janu Setiyowati; Henny Indreswari (Universitas Negeri Malang, 2024)
Abstract: Early dating or dating at an early age is carried out on individuals who are less than 14 years old. Early dating has a big impact because the perpetrator is still not mature enough to make decisions and has not yet reached emotional stability. Elementary school students who do early dating do not know that all forms of action taken must be accounted for. They only follow the fun and trends in social circles. This problem is the basis for the importance of providing education about the impact of early sex as a step to prevent early dating at SD Negeri Banjararum 2 Singosari. This service is carried out by presenting material and continuing with sociodrama. The results of the service implementation showed that 98.9% of students understood the material presented, and 95.9% of students were interested and happy with the material presented. Abstrak: Early dating atau berpacaran pada usia dini dilakukan pada individu yang berumur kurang dari 14 tahun. Early dating mempunyai dampak yang begitu besar melihat pelaku masih belum cukup dewasa dalam mengambil keputusan dan belum mencapai kestabilan emosi. Para siswa SD yang melakukan early dating tidak mengetahui segala bentuk tindakan yang dilakukan harus dipertanggungjawabkan. Mereka hanya menuruti kesenangan dan trend dikalangan pergaulan sosial. Permasalahan tersebut menjadi dasar pentingnya memberikan edukasi mengenai dampak seks usia dini sebagai langkah untuk mencegah terjadinya early dating di SD Negeri Banjararum 2 Singosari. Pengabdian ini dilaksanakan dengan pemaparan materi dan dilanjutkan dengan sosiodrama. Hasil pelaksanaan pengabdian menunjukkan 98,9% siswa memahami materi yang disampaikan, serta 95,9% siswa tertarik dan senang dengan materi yang disampaikan.